2014
DOI: 10.1093/hmg/ddu249
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-12 ablation preserves muscle function in the mdx mouse

Abstract: Duchenne muscular dystrophy (DMD) is a devastating muscle wasting disease caused by mutations in dystrophin. Several downstream consequences of dystrophin deficiency are triggers of endoplasmic reticulum (ER) stress, including loss of calcium homeostasis, hypoxia and oxidative stress. During ER stress, misfolded proteins accumulate in the ER lumen and the unfolded protein response (UPR) is triggered, leading to adaptation or apoptosis. We hypothesized that ER stress is heightened in dystrophic muscles and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 67 publications
(57 reference statements)
10
37
0
Order By: Relevance
“…Previous studies have demonstrated that activation of caspase-12 occurs prior to the activation of executioner caspase-3 in the apoptosis of various cells associated with ER-stress (17,18,27). Consistent with the results of previous studies (11), the protein level of cleaved caspase-12 was increased following the same concentration of V8 stimulation in the present study.…”
Section: A B C Dsupporting
confidence: 93%
“…Previous studies have demonstrated that activation of caspase-12 occurs prior to the activation of executioner caspase-3 in the apoptosis of various cells associated with ER-stress (17,18,27). Consistent with the results of previous studies (11), the protein level of cleaved caspase-12 was increased following the same concentration of V8 stimulation in the present study.…”
Section: A B C Dsupporting
confidence: 93%
“…Although a recent report showed increased GRP78/BiP and CHOP proteins in muscle of mdx mice and that ER stress-related caspase activity and apoptosis contributes to mdx pathology [15], this is the first study to provide insight into all three canonical pathways of UPR activation in conjunction with measures of oxidative stress and heat shock protein defense. Notably, the importance of ER stress to the pathology of mdx mice is consistent with other dystrophy studies reporting ER stress in sporadic inclusion body myositis (s-IBM) [41] and tibial muscular dystrophy (TMD) [42].…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, a recent study showed that glucose regulated protein 78 (GRP78/BiP), which is a triggering factor for ER stress/UPR activation, was associated with ER-related apoptosis signaling in human DMD muscle and/or mdx mice [15]. A more thorough understanding of these processes in muscular dystrophy would provide further insight into the role these factors may play in mediating the disease pathology in order to develop new therapeutic tools.…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-12 has been detected only in mouse tissues, and caspase-4 may be its functional counterpart in humans. 33 The elucidation of mouse caspase-12 function may reveal the nature of caspase-4 in humans.…”
Section: Doxorubicin Induces Er Stress-initiated Apoptotic Signalingmentioning
confidence: 99%